ULSOnt: Ontology in IntelliRehab system: Development of ontology for Intelligent Rehabilitation system - Afandi R.R.; Radman A.; Bahari M.; Zakaria L.Q.; Mustapha M.; Ismail W. (SciTePress, 2024)
Indexed by Scopus